1996
DOI: 10.1177/10454411960070020101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Pulpo-Dentin Complex

Abstract: Dentin has a relatively high water content due to its tubular structure. Once dentin is exposed, this intratubular water is free to move in response to thermal, osmotic, evaporative, or tactile stimuli. Fluid shifts across dentin are thought to cause sufficient shear forces on odontoblasts, nerve endings, nearby fibroblasts, and blood vessels to cause significant mechanical irritation, disruption, or damage, depending on the magnitude of the fluid shift. Even in the absence of fluid shifts, the water-filled tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
255
1
57

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(317 citation statements)
references
References 155 publications
(208 reference statements)
4
255
1
57
Order By: Relevance
“…32 In spite of these chemical differences between dentin and pulp, the two are functionally coupled and hence are integrated as a tissue. 33 When normal teeth are subjected to any type of insult or trauma the pulp responds to these insults, for a short-term by an inflammatory response, and in the long-term by inducing the cytodifferentiation of odontoblast-like cells to produce reparative dentin as a biologic response to reduce the permeability of the pulpdentin complex and to restore it to its original sequestration. 33 In order to generate normal dentin-like tissue, the first requirement would be to mimic the physiologic environment.…”
Section: Dentin Matrix Protein 1 Induces Cytodifferentiation a Almushmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In spite of these chemical differences between dentin and pulp, the two are functionally coupled and hence are integrated as a tissue. 33 When normal teeth are subjected to any type of insult or trauma the pulp responds to these insults, for a short-term by an inflammatory response, and in the long-term by inducing the cytodifferentiation of odontoblast-like cells to produce reparative dentin as a biologic response to reduce the permeability of the pulpdentin complex and to restore it to its original sequestration. 33 In order to generate normal dentin-like tissue, the first requirement would be to mimic the physiologic environment.…”
Section: Dentin Matrix Protein 1 Induces Cytodifferentiation a Almushmentioning
confidence: 99%
“…33 When normal teeth are subjected to any type of insult or trauma the pulp responds to these insults, for a short-term by an inflammatory response, and in the long-term by inducing the cytodifferentiation of odontoblast-like cells to produce reparative dentin as a biologic response to reduce the permeability of the pulpdentin complex and to restore it to its original sequestration. 33 In order to generate normal dentin-like tissue, the first requirement would be to mimic the physiologic environment. For this, there should be cells that are competent and able to incorporate signals that are responsible for their cytodifferentiation to odontoblastlike cells, next there should be suitable induction signal(s) that will be able to induce these competent cells.…”
Section: Dentin Matrix Protein 1 Induces Cytodifferentiation a Almushmentioning
confidence: 99%
“…35 The shear strength of dentin differs in the central and cusp areas and is dependent on dentinal tubule orientation in the central area. 36 However, tubule orientation has no appreciable effect on the elastic behavior of normal dentin, as intertubular dentin governs the elastic behavior of the dentin substrate.…”
mentioning
confidence: 99%
“…However, long-term studies have shown that the rate of tooth loss is higher for endodontically treated teeth compared to nontreated teeth, due to fracture, secondary caries and complex restoration-associated problems [5,6,7,8]. This has been one of the central challenges in dentistry, and thus the improvement of antimicrobial agents and restorative materials and the diagnosis of pulp vitality to facilitate the control of infection are great interest [9]. The treatment of irreversible pulpitis aims to restore the original architecture and biological function of the infected pulp tissue by facilitating repair or by allowing for tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%